Update of the human secretoglobin (SCGB) gene superfamily and an example of 'evolutionary bloom' of androgen-binding protein genes within the mouse Scgb gene superfamily - Jackson Brian C; Thompson David C; Wright Mathew W; McAndrews Monica; Bernard Alfred; Nebert Daniel W; Vasiliou Vasilis (Human Genomics, 2011)
Abstract The secretoglobins (SCGBs) comprise a family of small, secreted proteins found in animals exclusively of mammalian lineage. There are 11 human SCGB genes and five pseudogenes. Interestingly, mice have 68 Scgb genes, four of which are highly orthologous to human SCGB genes; the remainder represent an 'evolutionary bloom' and make up a large gene family represented by only six counterparts in humans. SCGBs are found in high concentrations in many mammalian secretions, including fluids of the lung, lacrimal gland, salivary gland, prostate and uterus. Whereas the biological activities of most individual SCGBs have not been fully characterised, what already has been discovered suggests that this family has an important role in the modulation of inflammation, tissue repair and tumorigenesis. In mice, the large Scgb1b and Scgb2b gene families encode the androgen-binding proteins, which have been shown to play a role in mate selection. Although much has been learned about SCGBs in recent years, clearly more research remains to be done to allow a better understanding of the roles of these proteins in human health and disease. Such information is predicted to reveal valuable novel drug targets for the treatment of inflammation, as well as designing biomarkers that might identify tissue damage or cancer.